1992
DOI: 10.1177/004051759206201102
|View full text |Cite
|
Sign up to set email alerts
|

Deflection-Force Measurements and Observations on Kevlar 29® Parachute Fabrics

Abstract: Deflection-force relations for plain weave Kevlara fabrics have been determined under conditions of uniaxial loading. In these experiments, the loading is stopped at a given level and a portion of the fabric is encapsulated. The fabric is then unloaded, sectioned, and photographed. Measurements on the photographs reveal the changes in weave geometry and yam cross section with loading. The initial geometrical data are used in a large deformation mechanical model, which couples yam bcnding and stretching effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The latter quantify the macro-scale Poisson effect induced by the small-scale crimping and decrimping of the yarns. All calculations were performed using the yarn data for a particular weave of Kevlar ® 29 [13]. These data are shown in Table 1 with the reference elastica shapes given by…”
Section: Elastica Modelmentioning
confidence: 99%
“…The latter quantify the macro-scale Poisson effect induced by the small-scale crimping and decrimping of the yarns. All calculations were performed using the yarn data for a particular weave of Kevlar ® 29 [13]. These data are shown in Table 1 with the reference elastica shapes given by…”
Section: Elastica Modelmentioning
confidence: 99%
“…Parachute textiles are during use exposed to a series of rapid events during the opening of the parachute and handling during descent, which can lead to their frictional and thermal damages which at limit cause to catastrophic failure [1][2][3][4]. In addition to standard textile tests, which are standardized, it is also necessary to develop or to modify tests that better characterize dynamic manifestations, surface structure and resistance to air flow in conditions simulating real conditions during use [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies can be found on predicting fabric strength. These studies in general have concentrated on matters relating to the canopy of parachutes [1][2][3][4][5][6][7][8][9]. Edberg [1] studied the stress-strain curves of ultraviolet-aged nylon parachute fabrics where as Ericksen [4] studied the effects of folding on the strength of parachute materials.…”
mentioning
confidence: 99%